Atmospheric deposition of organic matter at a remote site in the central Mediterranean Sea: implications for the marine ecosystem - Y. Galletti; S. Becagli; A. di Sarra; M. Gonnelli; E. Pulido-Villena; D. M. Sferlazzo; R. Traversi; S. Vestri; C. Santinelli (Biogeosciences, 2020)
Atmospheric fluxes of dissolved organic matter (DOM) were studied for the first time on the island of Lampedusa, a remote site in the central Mediterranean Sea (Med Sea), between 19 March 2015 and 1 April 2017. The main goals of this study were to quantify total atmospheric deposition of DOM in this area and to evaluate the impact of Saharan dust deposition on DOM dynamics in the surface waters of the Mediterranean Sea. Our data show high variability in DOM deposition rates without a clear seasonality and a dissolved organic carbon (DOC) input from the atmosphere of 120.7 mmol DOC m−2 yr−1. Over the entire time series, the average dissolved organic phosphorus (DOP) and dissolved organic nitrogen (DON) contributions to the total dissolved pools were 40 % and 26 %, respectively. The data on atmospheric elemental ratios also show that each deposition event is characterized by a specific elemental ratio, suggesting a high variability in DOM composition and the presence of multiple sources. This study indicates that the organic substances transported by Saharan dust on Lampedusa mainly come from a natural sea spray and that Saharan dust can be an important carrier of organic substances even though the load of DOC associated with dust is highly variable. Our estimates suggest that atmospheric input has a larger impact on the Med Sea than on the global ocean. Further, DOC fluxes from the atmosphere to the Med Sea can be up to 6 times larger than total river input. Longer time series combined with modeling would greatly improve our understanding of the response of DOM dynamics in the Med Sea to the change in aerosol deposition pattern due to the effect of climate change.